Rancang Bangun Purwarupa Alat Penghitung Uang Logam Otomatis Dengan Sensor Multi Coin Acceptor Berbasis IoT - Stiyawan, Riki; Pramana, Rimba Nur Ramadhani; Wiguna, I Gede Nova; Jasa, Lie; Nugraha, I Putu Elba Duta; Rahardjo, Pratolo (Majalah Ilmiah Teknologi Elektro; Vol 23 No 2 (2024): (Juli - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2024.v23i02.P01, 2024)
Money is an object that can be exchanged for other goods, used as a means to assess the value of goods, and can be stored. There are two physical forms of money still commonly used today, one of which is coins. Counting coins manually is prone to human error and can be time-consuming, especially when dealing with a large number of coins. One solution is to design an IoT- based automatic coin counter. This research aims to design an IoT- based automatic coin counter that can help accurately count coins in various applications, such as vending machines and cash registers. The device uses a multi-coin acceptor sensor to detect and identify different types of coins, with an ESP32 microcontroller as the main controller and an IoT-based communication module to send data to a server. The developed software allows sensor data to be processed and displayed through a web-based user interface. Test results show that this device can detect and count Indonesian Rupiah coins with 100% accuracy and makes it easier for users to monitor the total amount of coins collected. This research successfully achieved its goal by producing a device that is accurate and efficient in counting coins from the four tested denominations: Rp100, Rp200, Rp500, and Rp1000.